1989
DOI: 10.1902/jop.1989.60.9.506
|View full text |Cite
|
Sign up to set email alerts
|

Actinobacillus actinomycetemcomitans Serotypes and Leukotoxicity in Korean Localized Juvenile Periodontitis

Abstract: actinobacillus actinomycetemcomitans is thought to play an important role in the pathogenesis of localized juvenile Periodontitis (LJP). Preliminary data suggested that the serotype distribution of A. actinomycetemcomitans in Korea and the United States differ. This study evaluated A. actinomycetemcomitans prevalence, serotype distribution, and leukotoxicity in Korean LJP patients by culture, enzyme‐linked immunosorbent assay, indirect immunofluorescence, and lactate dehydrogenase release from polymorphonuclea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
52
1
1

Year Published

1994
1994
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(57 citation statements)
references
References 39 publications
3
52
1
1
Order By: Relevance
“…An analysis of a larger study population exhibiting multiple simultaneous clones of A. actinomycetemcomitans is warranted and may reveal associations with other variables, such as age, periodontal status, and ethnicity. Multiple intra-individual serotypes have been previously detected by Chung and collegues in 3 of the 9 (33%) Korean subjects 21 and Ebersole et al in 4 of the 30 (11%) American-Hispanic subjects studied. 22 Contradictory results were earlier obtained by Zambon et al, 23 who serotyped 301 A. actinomycetemcomitans isolates from 74 American subjects and failed to detect multiple intra-individual serotypes or non-serotypeable isolates by using serotype-specific rabbit antisera raised against serotypes a through c.…”
Section: Discussionmentioning
confidence: 77%
“…An analysis of a larger study population exhibiting multiple simultaneous clones of A. actinomycetemcomitans is warranted and may reveal associations with other variables, such as age, periodontal status, and ethnicity. Multiple intra-individual serotypes have been previously detected by Chung and collegues in 3 of the 9 (33%) Korean subjects 21 and Ebersole et al in 4 of the 30 (11%) American-Hispanic subjects studied. 22 Contradictory results were earlier obtained by Zambon et al, 23 who serotyped 301 A. actinomycetemcomitans isolates from 74 American subjects and failed to detect multiple intra-individual serotypes or non-serotypeable isolates by using serotype-specific rabbit antisera raised against serotypes a through c.…”
Section: Discussionmentioning
confidence: 77%
“…[6][7][8] In the review of Slots and Ting, 9 a large number of studies reported that this bacterium was isolated in periodontal lesions from 75% to 100% of LAgP. A. actinomycetemcomitans is considered the primary pathogen of AgP, especially in the localized form, even when known as juvenile periodontitis or early-onset periodontitis.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results have been obtained in studies from China, 18 Chile, 10 and the United Kingdom. [6][7][8]29,34 Although P. intermedia has not been investigated extensively, it has also been associated with AgP in a number of studies. [6][7][8]29,34 Although P. intermedia has not been investigated extensively, it has also been associated with AgP in a number of studies.…”
Section: Discussionmentioning
confidence: 99%
“…Ethnicity and sociodemographic status have been shown to affect the carriage patterns of periodontal pathogens. 11,16,17 Childhood and adolescence are critical time points for the onset of AgP. The two main diagnostic criteria used for the detection of periodontitis are the loss of connective tissue attachment and loss of alveolar bone based on clinical and radiographic assessments.…”
Section: Periodontal Diseasesmentioning
confidence: 99%